Case Report: Streptococcus dysgalactiae ssp. dysgalactiae bloodstream infections in patients with breast cancer after radiotherapy and chemotherapy - Tian, Chongmei; Dong, Su; You, Zhixin; Zhao, Yaping; Xu, Hongfeng; Chen, Jingbai; Fang, Yuejuan (Frontiers in Medicine, 2025)
Bloodstream infections are life-threatening conditions in patients with breast cancer, especially among older individuals. Although the most common risk factor in these patients with tumors is the use of severe neutropenia secondary to myelosuppressive chemotherapy and radiotherapy, other factors are possibly associated with the invasive pathogenicity of microorganisms, including Streptococcus dysgalactiae. Streptococcus dysgalactiae ssp. dysgalactiae (SDSD) has been considered both an environmental pathogen and a contagious pathogen. However, there have been few reports of bloodstream infections with SDSD in patients with breast cancer after radiotherapy and chemotherapy. In this study, we report an interesting case of bloodstream infection caused by SDSD in an older patient with breast cancer after radiotherapy and chemotherapy. A 60-year-old Chinese woman had a history of breast cancer for 2 years. She developed chills and fever after puncturing blood blisters in the mouth, accompanied by fatigue and poor appetite. After 6 days of antimicrobial therapy, the patient showed gradual recovery. Bloodstream infections with SDSD in patients with breast cancer are rare. Therefore, accurate diagnosis and timely treatment can be lifesaving.